P. 1
Untitled

Untitled

|Views: 5|Likes:
Published by api-150839388

More info:

Published by: api-150839388 on May 30, 2013
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

09/28/2013

pdf

text

original

3 No.

1 2011 / — —
1
(1) A =
_
_
_
2 −1 2 −2
4 −1 4 −2
6 −1 6 −2
_
_
_
=
_
_
_
1 0
3 2
5 4
_
_
_
, B =
_
(−1)
1
(−1)
2
(−1)
3
(−1)
2
(−1)
4
(−1)
6
_
=
_
−1 1 −1
1 1 1
_
(2) (1) 2X = 2
t
A + B = 2
_
1 3 5
0 2 4
_
+
_
−1 1 −1
1 1 1
_
=
_
2 6 10
0 4 8
_
+
_
−1 1 −1
1 1 1
_
=
_
1 7 9
1 5 9
_
X =
1
2
_
1 7 9
1 5 9
_
2
(1) (1 0)
_
2
53
_
= 1 · 2 + 0 · 53 = 2
(2)
_
_
_
2
1
−1
_
_
_
(5 3 −1) =
_
_
_
2 · 5 2 · 3 2 · (−1)
1 · 5 1 · 3 1 · (−1)
−1 · 5 −1 · 3 −1 · (−1)
_
_
_
=
_
_
_
10 6 −2
5 3 −1
−5 −3 1
_
_
_
(3)
_
2 6 1
2 1 2
_
_
_
_
1 0
0 1
2 3
_
_
_
=
_
2 + 2 6 + 3
2 + 4 1 + 6
_
=
_
4 9
6 7
_
3
_
_
_
1 3 5 −1
3 5 −1 1
−1 −4 2 2
_
_
_
3 +1
−−−−−−→
2 -1 ×3
_
_
_
1 3 5 −1
0 −4 −16 4
0 −1 7 1
_
_
_
2 -3 ×4
−−−−−−→
_
_
_
1 3 5 −1
0 0 −44 0
0 −1 7 1
_
_
_
2 ×
−1
44
−−−−−→
2 ⇔3
_
_
_
1 3 5 −1
0 −1 7 1
0 0 1 0
_
_
_
_
¸
¸
¸
_
¸
¸
¸
_
x + 3y + 5z = −1
−y + 7z = 1
z = 0
_
¸
¸
¸
_
¸
¸
¸
_
x = 2
y = −1
z = 0
4
(1) (A|E) =
_
_
_
1 2 1 1 0 0
2 3 1 0 1 0
1 2 2 0 0 1
_
_
_
2 1 ×2
−−−−−−−→
3 -1
_
_
_
1 2 1 1 0 0
0 −1 −1 −2 1 0
0 0 1 −1 0 1
_
_
_
1 3
−−−−−−→
2 +3
_
_
_
1 2 0 2 0 −1
0 −1 0 −3 1 1
0 0 1 −1 0 1
_
_
_
1 +2 ×2
−−−−−−−→
2 ×(−1)
_
_
_
1 0 0 −4 2 1
0 1 0 3 −1 −1
0 0 1 −1 0 1
_
_
_
A
−1
=
_
_
_
−4 2 1
3 −1 −1
−1 0 1
_
_
_
(2) A
_
_
_
x
y
z
_
_
_
=
_
_
_
1
0
2
_
_
_
A
−1
(1)
_
_
_
x
y
z
_
_
_
= A
−1
_
_
_
1
0
2
_
_
_
=
_
_
_
−4 2 1
3 −1 −1
−1 0 1
_
_
_
_
_
_
1
0
2
_
_
_
=
_
_
_
−4 + 2
3 −2
−1 + 2
_
_
_
=
_
_
_
−2
1
1
_
_
_
5
(1) A =
_
_
_
1 1 0
0 1 1
0 0 1
_
_
_
=
_
_
_
1 0 0
0 1 0
0 0 1
_
_
_
+
_
_
_
0 1 0
0 0 1
0 0 0
_
_
_
= E +T
(2) E
n
= E T
1
= T, T
2
=
_
_
_
0 1 0
0 0 1
0 0 0
_
_
_
_
_
_
0 1 0
0 0 1
0 0 0
_
_
_
=
_
_
_
0 0 1
0 0 0
0 0 0
_
_
_
, T
3
= T
2
T =
_
_
_
0 0 1
0 0 0
0 0 0
_
_
_
_
_
_
0 1 0
0 0 1
0 0 0
_
_
_
=
_
_
_
0 0 0
0 0 0
0 0 0
_
_
_
= O n ≥ 3 T
n
= O
(3) A
1
= A =
_
_
_
1 1 0
0 1 1
0 0 1
_
_
_
ET = TE = T (1),(2) A
2
= (E +T)
2
= E
2
+
2T +T
2
=
_
_
_
1 2 1
0 1 2
0 0 1
_
_
_
n ≥ 3 2 A
n
= (E +T)
n
=
n

k=0
n
C
k
E
n−k
T
k
=
n
C
0
E
n
T
0
+
n
C
1
E
n−1
T
1
+
n
C
2
E
n−2
T
2
+ O = E + nT +
n(n −1)
2
_
_
_
0 0 1
0 0 0
0 0 0
_
_
_
=
_
_
_
1 n
n(n−1)
2
0 1 n
0 0 1
_
_
_
n = 1, 2 n

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->